Receptor for advanced glycation end products: its role in Alzheimer’s disease and other neurological diseases - Lue, Lih-Fen (2009)
The receptor for advanced glycation end products (RAGE) has been demonstrated to play a central role in the pathogenic mechanisms of a growing number of important neurological diseases, including Alzheimer’s disease (AD) and stroke. Two functional types of RAGE have been associated with neurological diseases: cell membrane-bound (full length) and soluble. In general, ligand binding to full-length RAGE initiates sustained cellular activation and receptor-dependent signaling resulting in inflammation and cellular stress, and is ultimately associated with increased RAGE expression. By comparison, soluble forms of RAGE, generated either by alternative splicing or by proteolysis, can reduce the severity of the consequence of ligand-membrane RAGE interactions by preventing ligands from binding to the full-length RAGE. This can inhibit the neurotoxic or proinflammatory responses involved in disease states. This article reviews the pathobiology of RAGE, with emphasis on soluble forms of RAGE, and discusses its relevance to AD and to other neurological diseases, as well as how manipulation of the different forms of RAGE is becoming a powerful therapeutic strategy.